2013
DOI: 10.4236/jmmce.2013.12010
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behavior of Cu-Zn-Ni Shape Memory Alloys

Abstract: Four shape memory alloys of Cu-Zn-Ni, in the range of 35 -55 wt% of Cu, 43 -60 wt% Zn and 2 -9 wt% Ni, were prepared by ingot metallurgy route in an induction furnace under an inert atmosphere. The shape memory effect was tested by bend test. The alloys were further tested for its corrosion behavior in fresh water, Hank's solution and sea water. From the results it was observed that the alloys exhibit high corrosion resistance in fresh water when compared to Hank's solution and sea water. And it was also obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Silver for alloy (B1) to alloy (B5), when comparing the results of silver content (5%) (Micro and Nano particle), it was found that the linear attenuation coefficient of alloy (B5) increases compared to the linear attenuation of alloy (C5) due to the silver content ( Nano particle) compared with the sizes of the particles of the elements constituting the alloy, as the voids are filled and the inter-atomic spaces are reduced, which leads to an increase in the practical density and hardness and a decrease in porosity. Figure (14) show the direct relationship between the mass attenuation coefficient and the silver content of the alloys (C1, C2, C3, C4, C5), as the mass attenuation coefficient increases by (33.5%) when the silver content is increased from (1-5)% to the effect of silver particles Its role is to fill in the blanks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Silver for alloy (B1) to alloy (B5), when comparing the results of silver content (5%) (Micro and Nano particle), it was found that the linear attenuation coefficient of alloy (B5) increases compared to the linear attenuation of alloy (C5) due to the silver content ( Nano particle) compared with the sizes of the particles of the elements constituting the alloy, as the voids are filled and the inter-atomic spaces are reduced, which leads to an increase in the practical density and hardness and a decrease in porosity. Figure (14) show the direct relationship between the mass attenuation coefficient and the silver content of the alloys (C1, C2, C3, C4, C5), as the mass attenuation coefficient increases by (33.5%) when the silver content is increased from (1-5)% to the effect of silver particles Its role is to fill in the blanks.…”
Section: Resultsmentioning
confidence: 99%
“…Some copper alloys are designed for use in safety and protection devices to stop the flow of toxic or flammable gases and have also been used in structural or The semi-structure to improve its resistance in addition to its use in the connections designated for air conditioning systems for its ability to remember the shape when heated to high temperatures and return to its original shape after cooling. The basis of this effect is the transformation of alloys from the martensite phase to the austenite phase [14,15].…”
Section: Attenuationmentioning
confidence: 99%
“…Shape memory alloys (SMAs) have wide applications in thermal sensors, protection devices, medical devices, and others due to their unique properties such as Super Elasticity, and the shape memory effect (SMAs), and to improve their properties, limited quantities of some alloying elements are added to them individually or jointly. The basis of the effect is the transformation of the alloys from the martensite phase to another austenite phase when it is heated to high temperatures and returned to its original shape after cooling, [15,16].…”
Section: Memory Alloys For Shapementioning
confidence: 99%
“…In realistic applications, as the alloy is exposure to corrosion solution for a period of time they are exhibit to corrosion and pitting, for that reason study of corrosion behaviour like corrosion current and potential and pitting potential of the alloys are require to be done before they are put into biomedical and industrial applications. Since SMAs find a wide application in the marine, aerospace applications and it is also used in the surgical medical use such as guide wire, so it becomes necessary that the shape memory alloys high corrosion resistance to the environment in which it is being used, so it is important to evaluate the corrosion behaviour of the SMAs [11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%